Using Sources in the History Classroom for Developing Students’ Historical and Critical Thinking (action research) - Minasyan, Lilit (History and Culture, 2021)
The article examines the impact of using primary and secondary sources during history classes to develop learners’ historical and critical thinking. The author starts from the research hypothesis that the skills needed and developed while working with various sources contribute to the development of historical thinking and critical thinking as well as information analysis, interpretation, evaluation, and decision-making skills. The author tested the hypothesis in one of the schools of Yerevan during action research. The research results confirm the positive effect of the chosen method on developing the learners’ above-mentioned thinking skills and discuss specific difficulties and limitations that arise during its application.